Clinical and radiological features of mesenteric panniculitis: a critical overview - Buragina, Giuseppe; Magenta Biasina, Alberto; Carrafiello, Gianpaolo (Acta Biomedica Atenei Parmensis, 2019)
The mesenteric panniculitis is a rare form of inflammation that mainly involves the mesenteric adipose tissue. The etiology remains unknown and the disease has been associated with various conditions such as cancer, abdominal trauma, previous surgery, autoimmune diseases and obesity. Mesenteric panniculitis can be divided into two main groups: the mesenteric panniculitis with only the inflammation and degeneration of the mesenteric fat, and the retractile panniculitis, mainly fibrotic, with retraction of the surrounding structures. From a radiological point of view, there are two main signs: the fat ring sign, which is the presence of normal fat around vessels and lymph nodes, and the pseudocapsula around the lesion. In this paper, we present the imaging and clinical features of mesenteric panniculits with particular reference to the differential diagnosis and the possible etiological associations. (www.actabiomedica.it)